การขนส่งสินค้าน้ำตาลถุงต่อเนื่องหลายรูปแบบจากประเทศไทยไปกัมพูชา - เอกพล ประไพทรัพย์สกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
This thesis intended to evaluate efficiencies of procedure of the multimodal transportation of sugar bags from the sugar mill located in Saraburi to customers in Cambodia by 3 routes - take only trailer for the 1st route, take train & trailer for the 2nd route and take ship vessel & trailer for the 3rd route based on FCL basis and one of the sugar mills and distributors was selected for this study. The factors to be considered to evaluate the efficiencies of the transportation procedure for this study comprised the transportation cost, transit time in term of late money collection period s interest and transportation risk in term of loss & damage cost, determined by former theories and researches. Besides, the related facts were obtained by studying the work process and relevant documents. Upon study and result conclusion, the 3 factors - transportation cost, transit time and risk were compared within 3 routes to select the most efficient one by considering the least total cost. It appears that the 1st route is the most efficient with the least transit time and risk. In the mean time, the 2nd one is moderately efficient with the least transportation cost and the 3rd one is the least efficient with the highest transportation cost and the longest transit time. However, as for the risk factor, it was considered only the cause of accident leading to the loss and damage of goods.